The process, outcomes and context of the sanitation change induced by the Swachh Bharat Mission in rural Jharkhand, India - Novotný, Josef; Borde, Radhika; Ficek, František; Kumar, Anant (BMC public health, 2024)
BACKGROUND: The Indian Swachh Bharat Mission (SBM) was launched in 2014 with the goal to make India open defecation (OD) free by October 2019. Although it is known that the ambitious goal was not achieved, the nature of the sanitation change brought about by the SBM in different parts of India is poorly understood. One reason is a dearth of case studies that would shed light on the performance of the SBM simultaneously across its different domains. This article provides an example of such study. Employing a Process, Outcomes, Context approach, the objective is to understand the process and outcomes of the SBM-induced sanitation change in a specific context of rural Jharkhand. METHODS: The study utilizes data collected through field research conducted in the rural areas of Ranchi district, Jharkhand, a state in east-central India. This data was obtained via repeated cross-sectional household surveys conducted at the beginning and at the end of the SBM, supplemented by key informant interviews with SBM stakeholders. FINDINGS: We identified political support of SBM implementation and its acceptance amongst the population. Female community workers became key agents of SBM implementation at local level. The SBM increased toilet coverage in the study area from 15% to 85% and lowered the OD rate from 93% to 26%. It substantially reduced structural inequalities in access to toilets, furthered social sanitation norms, improved some of the attitudes towards toilet use, but impacted less on hygiene and sanitation knowledge. The implementation mainly concentrated on the construction of subsidized toilets but less on improving public understanding of safe sanitation practices. CONCLUSIONS: Although the SBM reduced sanitation inequalities in access to toilets in the study area, the behaviour change component was underplayed, focusing more on spreading normative sanitation messages and less on public education. Sustainability of the observed sanitation change remains a key question for the future. This article calls for more systematic production of geographically situated knowledge on the performance of sanitation interventions.
Keywords: Asijci; Aspirations, Psychological; Asian People; lidé; aspirace (psychologie); Cross-Sectional Studies; průřezové studie; sanitace; ženské pohlaví; Female; India; Humans; Sanitation; Indie